Indirect bonding technique in orthodontics - Kübra Yıldırım; Banu Sağlam Aydınatay (Gazi University, 2016)
'Direct Bonding Technique' which allows the fixed orthodontic appliances to be directly bonded to teeth without using bands decreased the clinic time for bracket bonding and increased esthetics and oral hygiene during orthodontic treatment. However, mistakes in bracket positioning were observed due to decreased direct visual sight and access to posterior teeth. 'Indirect Bonding Technique' was developed for eliminating these problems. Initially, decreased bond strength, higher bond failure rate, periodontal tissue irritation, compromised oral hygiene and increased laboratory time were the main disadvantages of this technique when compared to direct bonding. The newly developed materials and modified techniques help to eliminate these negative consequences. Today, the brackets bonded with indirect technique have similar bond strength with brackets bonded directly. Moreover, indirect and direct bonding techniques have similar effects on periodontal tissues. However, indirect bonding technique requires more attention and precision in laboratory and clinical stage, and has higher cost. Orthodontist's preference between these two bonding techniques may differ according to time spent in laboratory and clinic, cost, patient comfort and personal opinion.